Meningkatkan Karakter Religius Peserta Didik Di SMPN 3 Tanjung Bunga Melalui Kompetensi Kepribadian Guru Pendidikan Agama Katolik - keban, Yosep; Soi Leton , Susana; Kelara Welan, Maria Selvina (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2024)
The low religious character of the students became a serious problem in the field of education. It's also found at the SMPN 3 Tanjung Bunga-East Flores. From this point of view, there is a need for the role of the personality competence of the teacher of Catholic Education to be able to improve and enhance the religious character of the student. The aim is to know how to improve the religious character of the students of SMPN 3 Tanjung Bunga through the competence of the personality of PAK teachers. Data collected through interviews, documentation and observations were analyzed through phases of data reduction, data presentation, and conclusion-making. The research was conducted from June to August 2024. The results of this study said that the religious character of students at SMPN 3 Tanjung Bunga could be improved through the personality competence of PAK teacher. Therefore, the teachers needed to understand their personality competencies and students should also improve their religious character through the personality competencies of PAK teachers. This research is expected to contribute to the field of education, particularly in enhancing the religious character of students through the personality competencies of Catholic religious education teachers.